Tantangan Dan Peluang Layanan Berbasis Digital Di Desa Tambelang Kecamatan Touluaan Selatan - Jericho Danga Pombengi; Joyce Jacinta Rares; Jelita Manoppo; Kezia Pondaag; Elsa Waruis; Gilbert Sambur (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This research analyzes the obstacles and potential for the deployment of digitalized public services in Tambelang Village, South Touluaan District. A qualitative descriptive method was used, with data collected through interviews, observation, and documentation. Participants were selected purposive sampling from village officials and community members involved in public service delivery. The analysis refers to Indrajit's (2016) digital governance theory, which consists of three main dimensions: capacity, support, and value. The results indicate that digital service implementation in this village has not yet run optimally. The main obstacle is the lack of adequate infrastructure, particularly the absence of a stable internet network and frequent power outages that prevent communities from accessing digital services. In addition, low digital literacy among residents and limited technical skills of village staff cause manual methods to remain dominant in daily administrative practices. From the support dimension, policy commitment, training programs, and public socialization are still insufficient, even though village officials have shown a willingness to adopt digital systems. From the value dimension, digital services have great potential to accelerate administrative processes, expand public information access, and improve governance transparency. However, these benefits have not been fully realized due to existing infrastructure limitations. This study concludes that digital transformation in this village must be carried out gradually through infrastructure improvement, human resource development, and coordinated commitment from all stakeholders.